O espaço ficcional em As aves, de Aristófanes - Paulo César de Brito Teles Júnior (2017)
This dissertation presents a study of the construction of the fictional space of the play Birds, written by the comic playwright Aristophanes, taking into account the speech of its comic hero Pisthetaerus. The development of the study focuses on the fictional structure of space inthe literary text, the conception of space and the functions that it assumes in the course of the narrative alongside the discourse of the characters. The established research seeks to demonstrate that the spatial category of the piece in question reaches a different condition: through the lines of the character Pisthetaerus, we come into contact with a space that isinitially idealizied and receives Utopian dimensions. Nevertheless, we could see that this same space begins to acquire negative connotations, similar to those that affect the reality, especially the one of the city of Athens at the time in which this comedy had in its first presentation.